Structure and magneto transport study of La deficient La1.7Pr0.2CoFeO6 double perovskite - Singh P.; Gangwar V.K.; Alam M.; Chatterjee S. (My University, 2025)
The resistivity, dielectric constant, magneto-dielectric and complex impedance response of La deficient double perovskite La1.7Pr0.2CoFeO6 polycrystalline sample have been investigated. The obtained crystal structure of LPCFO is P21/n. Positive (~70%) magneto-resistance has been observed in this semiconducting sample. The giant dielectric constant (~104) with (~ -5%) negative magneto-dielectric constant is also obtained in this sample. The role of both grain and grain boundary in electrical properties for LPCFO has been confirmed by impedance analysis. © 2020 American Institute of Physics Inc.. All rights reserved.